Differences in Body Image of Bekasi City Teenagers Who Do Physical Glow Ups Reviewed from Gender - Raihan Saputra; Sameer Seth (Siber International Journal of Sport Education, 2024)
This study aims to determine the differences in adolescent body image from the gender who do physical glow up with the method of discrimination and confirmatory factor analysis (CFA). A total of 31 items were arranged to measure body image in the context of glow up. The results of the discrimination power analysis showed that three of the items tested had discrimination power in accordance with the phenomenon studied, so that it could be used to measure body image effectively. Furthermore, CFA is used to test the validity and reliability of the construction of the item. The findings of this study are expected to provide deeper insights into the factors that affect the body image of adolescent boys or women who do physical glow ups.